How the Turkish-Germans Construct Their Imagined Communities on Social Media? Textual Analysis of the Facebook Page “Turks in Germany” - Madenoglu,Dila Naz (2020)
Abstract One of the most crowded diasporic communities in Europe are the Turkish community, and the majority of them reside in Germany. Nowadays, social media platforms, such as Facebook, gives them the opportunity to get together online and help them to create online imagined communities via groups and pages on Facebook. For this study, we selected the “Turks in Germany” page on Facebook to examine. In accordance with this purpose, the selected page’s one-year activity is textually analyzed. We used qualitative content analysis and examined different discourses that are circulating on this page to construct an online imagined community, based on Benedict Anderson’s theory. The results suggest that, on the Turkish-German Facebook groups and pages the imagined community is mostly built in relation to the country of origin, rather than the country of residence.